Message - Al-Shamahy, Prof. Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2023)
My love for our journal, colleagues in our beloved UJPR, as well as for the researchers whose our journal was honored to have the platform to present their research, required me to say some of the words I wrote in order to describe them all: “Beautiful..rather wonderful, worthy, and it is true for us to say with our mouths full.. that it is splendor at its peak, the charm of its beauty, magnificence, and delicacy of its brilliance... It’s articles in this noble scientific platform, our beloved UJPR, the pioneering, promising, and renewed pictures are bright, delicate, and considerate. Elegant words... Thank you, the creative firefly that created these researches and scientific articles, which informed, entertained, persuaded, satiated our thirst, satisfy our desire, cured our passion with the sciences of pharmacy and medicine, and quenched the flames of our love for science and knowledge... God is the role of inspiring writers.” After that, in the previous issue of UJPR, I liked the distinction of what the dear daughter, the scholar, Dr. Rima Benatoui, as she warned us against falling into the trap of predatory reviews in an attractive location, as she said: “Researchers should deal with some laws, but fall into the trap of predatory reviews with attractive website, supposedly indexed in Scopus, all this torture distorts the art of research, and its main goal of interchange of information, as delaying its application in industries or hospitals”. I go back and say that success is continuity in giving and that we in our dear journal are committed to this and are committed to developing the journal and reaching the highest ranks and serving researchers by delivering their research to the corners of the earth and serving humanity by finding solutions to health problems that surround people from every aspect.